HUMAN PAPILLOMAVIRUS: A CROSS-SECTIONAL SURVEY ON KNOWLEDGE AND ATTITUDES AMONG STUDENTS OF UNDERGRADUATE HEALTH STUDIES - Salimović-Bešić, Irma; Mujkić, Selma; Pašalić, Arzija (Acta medicae Medianae, 2024)
The study aimed to assess the knowledge and attitudes of future healthcare professionals in Bosnia and Herzegovina (BIH) regarding the nature of human papillomavirus (HPV), HPV testing, and vaccination.This descriptive-analytical, prospective, cross-sectional survey was conducted using a standardised questionnaire among students in the first and third year of undergraduate studies considering different study programs at the Faculty of Health Studies, University of Sarajevo. The research resulted in 110 fully completed questionnaires. The percentage of students who had heard about HPV was 88.9% in the first year and 92.3% in the third year of health studies. Third-year students had better general knowledge of HPV (p = 0.007) and attitudes toward HPV testing (p = 0.009). Significant differences were in general knowledge of HPV among students of all study programs (p < 0.001) and in the knowledge of HPV testing (p = 0.001) and vaccination (p = 0.001). Health Care and Physiotherapy students had more knowledge and better attitudes when compared with other study programs.The level of knowledge about HPV infection among students in BIH is low regardless of study year and program. Targeted interventions in health education could have a positive impact on spreading knowledge about HPV and adopting preventive methods in the future.
Keywords: human papillomavirus, papillomavirus infection; students, vaccination, surveys, questionnaires